A more perfect union : the story of our Constitution - Maestro, Betsy; Maestro, Giulio (New York : Lothrop, Lee & Shepard Books, 1987)
Describes how the Constitution was drafted and ratified.
Children's Catalog (Wilson)
ALA Notable Books
School Library Journal
5.2
3-6
Keywords: United States. -- Constitutional Convention -- (1787) -- Juvenile literature; United States. -- Constitutional Convention -- (1787); United States -- Constitutional history -- Juvenile literature; United States -- Constitutional history; United States -- Constitutional history